A Molecular Analysis of Memory B Cell and Antibody Responses Against Plasmodium falciparum Merozoite Surface Protein 1 in Children and Adults From Uganda - S. Jake Gonzales; Kathleen N. Clarke; Gayani Batugedara; Rolando Garza; Ashley E. Braddom; Raphael A. Reyes; Isaac Ssewanyana; Isaac Ssewanyana; Kendra C. Garrison; Gregory C. Ippolito; Bryan Greenhouse; Sebastiaan Bol; et al. (Frontiers in Immunology, 2022)
Memory B cells (MBCs) and plasma antibodies against Plasmodium falciparum (Pf) merozoite antigens are important components of the protective immune response against malaria. To gain understanding of how responses against Pf develop in these two arms of the humoral immune system, we evaluated MBC and antibody responses against the most abundant merozoite antigen, full-length Pf merozoite surface protein 1 (PfMSP1FL), in individuals from a region in Uganda with high Pf transmission. Our results showed that PfMSP1FL-specific B cells in adults with immunological protection against malaria were predominantly IgG+ classical MBCs, while children with incomplete protection mainly harbored IgM+ PfMSP1FL-specific classical MBCs. In contrast, anti-PfMSP1FL plasma IgM reactivity was minimal in both children and adults. Instead, both groups showed high plasma IgG reactivity against PfMSP1FL, with broadening of the response against non-3D7 strains in adults. The B cell receptors encoded by PfMSP1FL-specific IgG+ MBCs carried high levels of amino acid substitutions and recognized relatively conserved epitopes on the highly variable PfMSP1 protein. Proteomics analysis of PfMSP119-specific IgG in plasma of an adult revealed a limited repertoire of anti-MSP1 antibodies, most of which were IgG1 or IgG3. Similar to B cell receptors of PfMSP1FL-specific MBCs, anti-PfMSP119 IgGs had high levels of amino acid substitutions and their sequences were predominantly found in classical MBCs, not atypical MBCs. Collectively, these results showed evolution of the PfMSP1-specific humoral immune response with cumulative Pf exposure, with a shift from IgM+ to IgG+ B cell memory, diversification of B cells from germline, and stronger recognition of PfMSP1 variants by the plasma IgG repertoire.